Photocatalytic oxidation of different aliphatic carboxylic acids by TiO₂ catalyst - Kaur, Manpreet (My University, 2014)
Among advanced oxidation processes, heterogeneous photocatalysis is a potential method based on UV/titanium dioxide for degradation of various recalcitrant chemical compounds. The dissertation work puts forward a method of UV based photocatalytic degradation (PCD) of long chain carboxylic acids, by bare and metal-doped TiO2. The evolution of carbon dioxide was analyzed using gas chromatography and volumetric acid-base titration method. The degradation studies using Ag-TiO₂/UV system indicate enhanced degradation rate by metal doped system when compared to bare TiO₂. In addition, increase in chain length of carboxylic acids significantly influenced the degradability of the compounds with reduced degradation on increase in chain length. During photocatalytic degradation process, complete oxidation of acids lead to formation of CO2. The rate of CO2 formation was dependent on carbon chain length and irradiation time with requirement of longer duration of irradiation for acids with longer carbon chain. This study can be helpful for designing photocatalytic reactors for removal of acids from industrial wastewaters and other effluents.
MS, SCBC
Keywords: Heterogeneous Ctaysis; Carboxylic acids; gas chromatography; carbon chain length